Context as Continuum - Adam Yarinsky (Oz, 2015)
Design, including architecture, is situated in a complex web of relationships that encompasses the full physical and social context for life on the planet. Acknowledging context as an ecology, it is also important to recognize that the boundaries between places, activities, and experiences have become blurred by the expanding virtual world and the shrinking planet.